Routledge International Handbook of Religion in Global Society - Cornelio, Jayeel (Archīum Ateneo, 2020)
Like any other subject, the study of religion is a child of its time. Shaped and forged over the course of the twentieth century, it has reflected the interests and political situation of the world at the time. As the twenty-first century unfolds, it is undergoing a major transition along with religion itself. The Routledge International Handbook of Religion in Global Society showcases new work and new approaches to religion which work across boundaries of religious tradition, academic discipline, and region. The influence of globalizing processes has been evident in social and cultural networking by way of new media like the internet, in the extensive power of global capitalism and in the increasing influence of international bodies and legal instruments. Religion has been changing and adapting too. This handbook offers fresh insights on the dynamic reality of religion in global societies today by underscoring transformations in eight key areas: Market and Branding; Contemporary Ethics and Virtues; Intimate Identities; Transnational Movements; Diasporic Communities; Responses to Diversity; National Tensions; and Reflections on ‘Religion’. These themes demonstrate the handbook’s new topics and approaches that move beyond existing agendas. Bringing together scholars of all ages and stages of career from around the world, the handbook showcases the dynamism of religion in global societies. It is an accessible introduction to new ways of approaching the study of religion practically, theoretically and geographically.